PENDAMPINGAN PENULISAN PUISI BAGI SISWA SMP/MTs KECAMATAN SURALAGA - Ramlah H.A Gani; Nurdin Nurdin; Titin Ernawati; Pujilestari Pujilestari (Gapenas Publisher, 2023)
This Community Service Program aims to provide training and guidance in the field of literary writing for students of SMP IT Pancor Kopong, MTs NW Dames, and MTs NW Getap, Suralaga District from April to July 2022. This activity is an effort to foster students' literacy skills, especially poetry writing skills. In addition, this activity is also a way to bring schools and students closer to literary works. In its implementation, this PkM is carried out by providing training and mentoring on an ongoing basis. The training was conducted for three days to students. Training is carried out in two ways, namely in-class (inside the class) and out-class (outside the class). In-class training is conducted to provide students with the same understanding of writing literary works, while out-class training is carried out to hone students' sensitivity, critical thinking, and intuition to capture every problem that exists around them to be used as material in writing literary works. Coaching is carried out by holding meetings for three days every week on an ongoing basis to provide stimulus and evaluate the work of participants/students. Here, work reviews, discussions, and improvements are carried out based on input from the supervisor. Each participant is required to write five literary works in this program. Based on the training and coaching conducted at the three schools, it had a positive impact on the development of poetry writing skills. 98% of students are able to write poetry well, this is evident from the results of the poems which are made based on the criteria, namely the beauty of typography, themes, variations, and content. This criterion already exists in the students' poetry results